If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(h + 3) = 25 Reorder the terms: 5(3 + h) = 25 (3 * 5 + h * 5) = 25 (15 + 5h) = 25 Solving 15 + 5h = 25 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + 5h = 25 + -15 Combine like terms: 15 + -15 = 0 0 + 5h = 25 + -15 5h = 25 + -15 Combine like terms: 25 + -15 = 10 5h = 10 Divide each side by '5'. h = 2 Simplifying h = 2
| ?/4=12.4 | | 4x+48=3x+8 | | 3x^4+4x^2-15=0 | | 2x-11+3x-47=180 | | 2x+11+3x-47=180 | | 27+7x-2=11x+1 | | 6x-5=2+13 | | 2(x+3)=5+3y | | 9y+y=9y-5 | | 8x-40+2x+20=180 | | 5(h-2)=48 | | log(4x+124)=3 | | 0.09xX=145.62 | | 4.5d-3.2=-18.5 | | 7x-40+9y=180 | | 1/4x-2=-6x5/12 | | (12x+2)=(18x-2) | | 4x+2=2x+14whatisx | | (12x+2)+(18x-2)=360 | | 7z+1-z=1+5z+7 | | y+2=-75(x+1) | | 2x/45 | | x(t)=x+120(t-6) | | 2x=90-3x | | 0=1/3x-4 | | (6y-2)+y=180 | | 7x-2=11x+1 | | y-5=150(x+4) | | 3(x+2)=3(2x+4) | | (X-2+4i)(x-2-4i)= | | 12m+3n-5m+10n= | | X*2/3=8/9 |